31 Patients', relatives' and health professionals' direct experiences and perceptions of bispectral index (BIS) monitoring in a UK hospice: a qualitative interview study for I-can-care. (13th October 2019) - Krooupa, Anna-Maria; Vivat, Bella; McKeever, Stephen; Stone, Patrick
Abstract : Background: Research interest is growing in using EEG-based tools, such as Bispectral Index (BIS) technology, to assess levels of sedation for palliative care patients. To date, little research has investigated using BIS in palliative care practice, but previous exploratory work for our I-CANCARE programme asked clinicians, patients, and relatives whether using BIS in palliative care would be acceptable in principle. Aim: To explore the direct experiences and perceptions of palliative care patients, their relatives, and clinicians regarding BIS monitoring in a UK hospice. Methods: We trialled the use of BIS with hospice inpatients, and then conducted semi-structured interviews with them, their relatives, and hospice clinicians. Interview transcripts were analysed following the framework method. Results: Ten patients, two relatives, and ten clinicians participated in individual interviews. Most (as in our previous hypothetical study) considered BIS monitoring non-intrusive. Some patients commented that after the sensor had been applied to their foreheads they were 'not aware' of it. Patients and clinicians commented that, although noticeable, the BIS device and sensor were small and easily handled, and felt that the monitoring did not affect patients' daily routines, nor care activities. After trialling BIS monitoring, participants said that they would have no objections to BIS being used as part of routine care, provided that it was beneficial for patients. Conclusions: Our participants perceived BIS technology as acceptable and feasible for monitoring hospice inpatients' consciousness levels. This indicates that further exploration of how this technology might contribute to palliative care practice would be appropriate, and valuable.